VIRAL INFECTION AND LIPOPOLYSACCHARIDE: PATHOLOGICAL AXIS "LUNGS-JOINTS" AS A POTENTIAL CAUSE OF OSTEONECROSIS - Constantin Viktorovich Bubley; Vladimir Alexievich Beloglazov; Igor Anatolievich Yatskov; Anna Anatolyevna Zayaeva (Медицинская иммунология)
AbstractThe article analyzes the effect of viral infections such as SARS-CoV-2 and lipopolysaccharide (LPS), a component of the cell wall of gram-negative bacteria, on the development of osteonecrosis through the pathological lung-joint axis. Viral infection causes damage to lung cells and vascular endothelium, which leads to inflammatory and coagulation disorders, increasing the risk of bone ischemia. LPS, interacting with TLR4 receptors, enhances the inflammatory response and disrupts the blood supply to bones, stimulating resorption and preventing bone formation. In addition, the article highlights the role of lung dysbiosis caused by viral infection, which increases inflammation and increases the permeability of barriers to endotoxins. Information was searched for the keywords "osteonecrosis and lipopolysaccharide", "Covid-19 virus and lipopolysaccharide-binding protein", "Viremia and osteonecrosis", "Lung microflora and LPS" in foreign and domestic scientometric databases such as e-Library and PubMed. The presented data suggest that the combination of imbalance of “lipopolysaccharide-binding systems”, impaired pulmonary barrier, viral aggression and LPS is an important aggravating pro-inflammatory factor. This combination forms a predisposition or full-fledged osteonecrosis, which makes the search for mechanisms of influence on these conditions, both individually and in combination, a promising scientific and clinical direction. This study focuses on the variety of mechanisms through which viral infections and bacterial lipopolysaccharides can affect bone tissue. Research shows that influencing these mechanisms can open up new avenues for the development of therapeutic strategies. The prospects of using targeted therapies to mitigate the negative effects of these interactions are also being considered. These data emphasize the importance of an integrated approach in the study and treatment of osteonecrosis, taking into account both infectious and inflammatory components of the process.